THE INFLUENCE OF SOCIAL IMPACT MODERATING VARIABLES ON COMMUNITY ATTITUDE RELATIONSHIP WILL HALAL TOURISM AND HALAL TOURIST INTEREST IN YOGYAKARTA - Silvi Sri Mulyani; Misbachul Munir; Muhammad Hanif Ibrahim (FEBI UIN Sunan Kalijaga, 2020)
This study aims to find out and empirically examine the effect of moderating variables of sosial impact on the relationship between community attitudes towards halal tourism and the interest in halal tours in Special Regions of Yogyakarta. The study sample consisted of 435 respondents from five districts in ten sub-districts in the Special Region of Yogyakarta, with each sub-district consisting of five respondents. Data collection techniques use random cluster sampling or random data collection, but there are groupings of respondents from gender and age. The results of testing the data show that the researchers' hypotheses are acceptable, where the public attitude towards halal tourism influences people's interest in halal tours. The existence of a moderating variable in the form of social impact also supports the relationship